Аналіз спектральної эффективности солитонных ефективності солітоних волз на основі фотонно-кристалічних волокон - Абіх, І. В. (ХНУРЕ, 2019)
The most important factors that affect throughput and communication range in modern fiber optic lines are the presence of nonlinear effects the fibers. One method of reducing the effects of nonlinear effects, and namely: increasing the ratio of the data transfer rate to the width spectral channel with an increase in signal power or spectral efficiency, is the use of solitons as pulses, carrying information. This report is devoted to the analysis of spectral the efficiency of soliton fiber based on photonic crystal fibers, what is the actual task